Characteristics and precipitation behavior of (Ti,V)(CxN1-x)-CrC3-MoS2 complex inclusions in GCr15 steel for cylindrical rollers of shield machine main bearings - Jinlong Wang; Wenrui Yang; Xiaohao Mei; Desheng Li; Hao Tian; Aiping Xiao; Zhengliang Xue (Journal of Materials Research and Technology)
To address the challenge of carbonitride inclusions precipitated during the solidification of GCr15 steel used in cylindrical rollers for shield machine main bearings, thermodynamic and kinetic models of solidification-induced inclusions were applied, supplemented by quantitative analyses employing SEM-EDS, optical microscopy, three-dimensional non-destructive electrolytic etching, and automated inclusion statistics. These analyses were conducted on both industrially produced GCr15 bearing steel samples and laboratory re-melted samples. The impacts of cooling rate and steel composition on the chemistry, number density, and size of carbonitride inclusions were comprehensively investigated. The inclusions are complex (Ti,V) (CxN1-x)-CrC3-MoS2 rather than simple TiN or Ti(CxN1-x). These inclusions exhibited a cubic structure and appeared dark red under optical microscopy. Under controlled laboratory conditions, an increase in the solidification cooling rate resulted in a marked rise in the number density of these complex inclusions, accompanied by a significant reduction in their average size. Thermodynamic calculations revealed that when the solid fraction reached approximately 0.88, the precipitation of carbonitrides led to the consumption of solute atoms, thereby generating inflection points in the concentration profiles of Ti, N, C, Cr, and other elements at the solidification front. The (Ti,V) (CxN1-x)-CrC3-MoS2 inclusions readily nucleated heterogeneously on Al2O3 cores and exhibited a propensity to form composite inclusions with MnS.